2011
DOI: 10.3109/0886022x.2011.581404
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Renal Failure on Gastrointestinal Motility: A Study on the Changes of Gastric Emptying, Small Intestinal Transit, Interdigestive Myoelectric Complex, and Fecal Water Content

Abstract: The GI motility of the CRF rats is obviously impaired. This finding may indicate that the effects of CRF on GI motility might be relatively prevalent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…In the present study, we therefore chose this model, and used the charcoal transport assay to objectively assess the effect of CKD on intestinal motility. The results showed that CKD induced a progressive decrease in the intestinal transit at all investigated time points, reaching statistical significance level on postoperative weeks 8 and 10, indicating that CKD could indeed decrease intestinal motility, which were consistent with the results reported by others [4,31].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the present study, we therefore chose this model, and used the charcoal transport assay to objectively assess the effect of CKD on intestinal motility. The results showed that CKD induced a progressive decrease in the intestinal transit at all investigated time points, reaching statistical significance level on postoperative weeks 8 and 10, indicating that CKD could indeed decrease intestinal motility, which were consistent with the results reported by others [4,31].…”
Section: Discussionsupporting
confidence: 81%
“…In the CKD progression, the intestine and CKD influence each other [1], and intestinal dysmotility often occurs [2][3][4]. In clinical practice, patients with in- testinal dysmotility could present some main symptoms including abdominal bloating and distension and a mix of nausea and vomiting [5].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, CRF is mainly caused by hypertension, glomerulonephritis, and diabetes mellitus 3, 4 . This condition is made worse by a deterioration in nutrition level caused by accumulation of uremic toxins and reduced food intake, which could be attributed to many factors, such as gastrointestinal congestion, loss of appetite, and reduced glomerular filtration rate 46 . Compared to patients with other chronic diseases, patients with CRF tend to require longer and more frequent hospitalizations which are associated with higher morbidity and mortality 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations suggested that there was impaired small intestinal motility [36], impaired intestinal barrier function [37], lower number of crypts, and reduction in epithelial cell in patients with chronic renal insufficiency [3]. In addition, patients with diabetic nephropathy might have more-serious diabetic neuropathy and microangiopathy, which are linked to serious mucosal injuries.…”
Section: Discussionmentioning
confidence: 99%